Genomic and Proteomic Evidence for the Presence of a Peroxisome in the Apicomplexan Parasite Toxoplasma gondii and Other Coccidia. (6th November 2017) - Moog, Daniel; Przyborski, Jude M; Maier, Uwe G
Abstract: Apicomplexans are successful parasites responsible for severe human diseases including malaria, toxoplasmosis, and cryptosporidiosis. For many years, it has been discussed whether these parasites are in possession of peroxisomes, highly variable eukaryotic organelles usually involved in fatty acid degradation and cellular detoxification. Conflicting experimental data has been published. With the age of genomics, ever more high quality apicomplexan genomes have become available, that now allow a new assessment of the dispute. Here, we provide bioinformatic evidence for the presence of peroxisomes in Toxoplasma gondii and other coccidians. For these organisms, we have identified a complete set of peroxins, probably responsible for peroxisome biogenesis, division, and protein import. Moreover, via a global screening for peroxisomal targeting signals, we were able to show that a complete set of fatty acid β-oxidation enzymes is equipped with either PTS1 or PTS2 sequences, most likely mediating transport of these factors to putative peroxisomes in all investigated Coccidia. Our results further imply a life cycle stage-specific presence of peroxisomes in T. gondii and suggest several independent losses of peroxisomes during the evolution of apicomplexan parasites.